Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan, Kinerja Keuangan, dan Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Risma Mufarohah; Dwiyani Sudaryanti; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research was conducted to provide information to potential investors that is useful as a consideration of aspects that need to be taken into account in investing. This study also aims to find out how Corporate Social Responsibility influences company value, financial performance, and earnings management. In this study, Corporate Social Responsibility is measured using the Corporate Social Responsibility Index (CSRIj), company value is measured using PBV (Price to Book Value), financial performance is measured using ROE (Return On Assets), and earnings management is measured using the working capital accrual formula. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period where the data in this research comes from secondary data obtained through a purposive sampling technique. Based on the calculation data, 210 companies were selected as samples. This research data has fulfilled the classical assumption test requirements. The results of the analysis using simple linear regression analysis show that Corporate Social Responsibility has a negative and significant effect on firm value and financial performance and Corporate Social Responsibility has a positive effect on earnings management.Keywords : Corporate social responsibility, company value, financial performance,                   earnings management.